Electrospray ionization and heterogeneous matrix effects in liquid chromatography/mass spectrometry based meta‐metabolomics: A biomarker or a suppressed ion?. (14th December 2020) - Ghosson, Hikmat; Guitton, Yann; Ben Jrad, Amani; Patil, Chandrashekhar; Raviglione, Delphine; Salvia, Marie‐Virginie; Bertrand, Cédric
Abstract : Rationale: Correct biomarker determination in metabolomics is crucial for unbiased conclusions and reliable applications. However, this determination is subject to several drifts, e.g. matrix effects and ion suppression in Liquid Chromatography/Mass Spectrometry (LC/MS)‐based approaches. This phenomenon provokes critical issues for biomarker determination, particularly during comparative studies dealing with samples exhibiting heterogeneous complexities. Methods: Occurrence of the issue was coincidentally noticed when studying the environmental impact of a complex bioinsecticide: Bacillus thuringiensis israelensis. The studied samples comprised insecticide‐spiked sediments and untreated control sediments. QuEChERS extractions followed by LC/ESI‐Q/ToF analyses were performed on sediments after 15 days of incubation. Meta‐metabolomes containing pesticide xenometabolites and sediment endometabolites were analyzed in depth using XCMS‐based computational data preprocessing. Multivariate statistical analyses (PCA, OPLS‐DA) and raw data crosschecks were performed to search for environmental biomarkers. Results: Multivariate analyses and raw data crosschecks led to the selection of nine metabolites as biomarker candidates. However, when exploring the mass spectra, co‐elutions were noticed between seven of these metabolites and multi‐charged macromolecules originating from the pesticide. Provoked false positives were thus suspected due to a potential ion suppression exclusively occurring in the spiked samples. A dilution‐based approach was then applied. It confirmed five metabolites as suppressed ions. Conclusions: Ion suppression should be considered as a critical issue for biomarker determination when comparing heterogeneous metabolic profiles. Raw chromatograms and mass spectra crosschecks are mandatory to reveal potential ion suppressions in such cases. Dilution is a suitable approach to filter reliable biomarker candidates before their identification and absolute quantification.